Now about all these women in the Swedish film industry - Wallenberg, Louise 1970-; Papadopoulou, Frantzeska; Koskinen, Maaret 1951-; Soila, Tytti 1951- (Bloomsbury Academic, 2024)
"This book investigates women's representation and work in the Swedish film industry, focusing on both historical and contemporary cases and women from a variety of theoretical perspectives and methods emanating from cinema studies, gender studies, ethnography, and law"--
Part one frameworks: the power of institutions -- The sex of the author: on authorship Frantzeska Papadapoulou -- Gendering film distribution Frantzeska Papadopoulou -- In the crossfire: Anna Serner and the Swedish Film Institute Maaret Koskinen -- Part two histories,herstories, and representation -- Women on screen I: 1910s-1960s Louise Wallenberg -- Women on screen II: 1970s-2010s Louise Wallenberg -- Part three Routines, Practices, and practitioners -- Making a living: on the working conditions and salaries for actors and extras within Swedish Film Produciton 1930-1955 Tytti Soila -- Bibi Lindström: "Easy to work with" Tytti Soila -- Lisa Langseth: "Make sure that what's in your heart is done, so it doesn't drown and stay in the heart" Maaret Koskinen
Includes bibliographical references and index
Keywords: Women motion picture producers and directors / Sweden; Women in the motion picture industry / Sweden / History; Women in motion pictures; Motion picture industry / Sweden